2016
DOI: 10.2147/hiv.s120979
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of antiretroviral therapy on renal and liver functions among HIV-infected patients: a retrospective study

Abstract: BackgroundThe emergence of highly active antiretroviral therapy (HAART) has dramatically improved quality of life in prolonging survival of human immunodeficiency virus (HIV)-infected patients on treatment in developed as well as developing countries. However, the main shortcoming of HAART in long-term use is its potential to cause liver and kidney derangements that may be life threatening. The drugs are actively accumulated in the proximal renal tubule resulting in functional disturbance with mitochondrial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
22
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
8
22
4
Order By: Relevance
“…Even though HIV/HBV co-infected patients are at an increased risk of developing liver fibrosis compared with HIV mono-infected individual [34], our findings revealed that co-infection was independent of liver fibrosis. The prevalence of hepatotoxicity was 7.8%, which compares with the 6.5% reported in Ethiopia [35], however, the higher rate in this study could be due to the presence of co-infection with HBV.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Even though HIV/HBV co-infected patients are at an increased risk of developing liver fibrosis compared with HIV mono-infected individual [34], our findings revealed that co-infection was independent of liver fibrosis. The prevalence of hepatotoxicity was 7.8%, which compares with the 6.5% reported in Ethiopia [35], however, the higher rate in this study could be due to the presence of co-infection with HBV.…”
Section: Discussioncontrasting
confidence: 72%
“…The use of tenofovir and/or lamivudine in ART combination for treating HIV complicated with HBV co-infection has been recommended irrespective of the immune state of the patients [36]. However, these drugs have been found to increase the risk of developing nephrotoxicity in these patients [35, 37, 38]. Therefore, assessment of the renal function prior to treatment has been recommended [16, 37].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that long-term use of antiretroviral therapy may cause histopathological and histomorphological changes in the liver and kidneys [2829], and the elevated serum creatinine and alanine aminotransferase (ALT) [30]. Therefore, it is necessary to evaluate the potential in vitro and in vivo toxicity of IBP-CP24.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been carried out in Cameroon [9,29,30] and out of Cameroon [14,15,23,[31][32][33] on hepatotoxicity but there is paucity data on HAART/ cART-inducedhepatotoxicity.…”
Section: Introductionmentioning
confidence: 99%